Characteristics of female world-class skaters associated with changes in skating speed and stroke parameters in the straight section for 3,000 m speed skating race - Kimura, Y.; Yokozawa, T.; Yuda, J. (Journal of High Performance Sport, 2020)
The purpose of this study was to identify the characteristics of female world-class skaters associated with the changes in skating speed and stroke parameters in the straight section for 3,000 m race in the speed skating international competition. Sixteen contestants were categorized into top (n=8) and second groups (n=8) according to the official records. The horizontal speeds of the end of the straight and curved sections of the skaters were recorded with the local position measurement system. In addition, 4 synchronized high-speed cameras (300 frames/s) were used to record the skaters' motions at the mid portion of the inner finishing straight lane in the initial phase (2nd or 3rd lap), middle phase (4th or 5th lap), and final phase (6th or 7th lap) and to calculate the skating velocity, stroke frequency, gliding time, push-off time, and stroke length. The skating velocity of the top group was significantly greater than that of the second group in each phase (p<0.001). In the middle phase, the skating velocity negatively correlated with stroke frequency (r=-0.53, p<0.05) and positively correlated with gliding time (r=0.62, p<0.01) and stroke length (r=0.71, p<0.01). In the final phase, the change in speed during the straight section positively correlated with stroke frequency (r=0.67, p<0.01), and negatively correlated with gliding time (r=-0.60, p<0.05) and stroke length (r=-0.64, p<0.01). The skaters who maintained large skating velocity in the middle phase would acquire a larger stroke length in the straight section by pushing-off the ice effectively. In the final phase, increasing the stroke frequency was important for suppression of the decrease in speed during the straight section.